Designing the Safe Reopening of US Towns Through High‐Resolution Agent‐Based Modeling (Adv. Theory Simul. 9/2021). Issue 9 (7th September 2021) - Truszkowska, Agnieszka; Thakore, Malav; Zino, Lorenzo; Butail, Sachit; Caroppo, Emanuele; Jiang, Zhong‐Ping; Rizzo, Alessandro; Porfiri, Maurizio
Abstract : COVID‐19 Agent‐Based Modeling Toward Safe Reopening As COVID‐19 vaccine is being rolled‐out, theory and simulation tools could assist public health authorities in reopening the economy. In article number 2100157, Agnieszka Truszkowska, Maurizio Porfiri, and co‐workers examine the role of the vaccination rate on the spreading of COVID‐19 in a high‐resolution, agent‐based model of the city of New Rochelle, NY. Image by Anna Sawulska and Maurizio Porfiri.